Peningkatan Produksi Perikanan Budidaya Dengan Penerapan Sistem Mina Padi Di Desa Sungai Besar Kecamatan Bunut Hulu, Kabupaten Kapuas Hulu - M. Idham Shilman; Slamet Tarno; Agus Setiawan; Muhammad Nasir; Rizal Akbar Hutagalung (Politeknik Negeri Pontianak, 2021)
Sungai Besar Village is one of the areas in Bunut Hulu Subdistrict, Kapuas Hulu Regency, West Kalimantan, which has considerable development potential in the fisheries sector. This is reinforced by the majority of people who have a livelihood as farmers and fish farmers. In addition, Sungai Besar Village is also one of the leading regions for the fisheries sector, especially tilapia and catfish. However, the rapid increase in population can cause limited production areas that can be used in various fields of fisheries. This encourages the intensification of efforts as one way of land utilization. One way that can be done is the application of the Minapadi fish culture system. This minapadi system has several advantages including an increase in community income through the existence of fish farming and more effective land use. The development of the fisheries sector, primarily the tilapia (Oreochromis niloticus) aquaculture business using the Minapadi system, is a solution in addressing land use issues and improving the economic community in the Kapuas Hulu Regency. In addition, Sungai Besar Village is expected to become a target village for the production of fish cultivation using the Minapadi system. The method that will be used in community service activities (PPM) is the method of assisting the transformation of science and application programs (training and counseling) related to the application of fish cultivation with the Minapadi system. Expected output in this activity is the community of Sungai Besar Village is able to implement fish farming with the Minapadi system. This is in the form of a method of fish cultivation that is able to maximize land use. Keywords : Aquaculture, Tilapia, Mina Padi, Sungau Besar Village